Pulse pressure variation guided fluid therapy during kidney transplantation: a randomized controlled trial - Alessandro De Cassai; Ottavia Bond; Silvia Marini; Giulio Panciera; Lucrezia Furian; Flavia Neri; Giulio Andreatta; Paolo Rigotti; Paolo Feltracco (Brazilian Journal of Anesthesiology, 2020)
Purpose: Kidney transplantation is the gold-standard treatment for end stage renal disease. Although different hemodynamic variables, like central venous pressure and mean arterial pressure, have been used to guide volume replacement during surgery, the best strategy still ought to be determined. Respiratory arterial Pulse Pressure Variation (PPV) is recognized to be a good predictor of fluid responsiveness for perioperative hemodynamic optimization in operating room settings. The aim of this study was to investigate whether a PPV guided fluid management strategy is better than a liberal fluid strategy during kidney transplantation surgeries. Identification of differences in urine output in the first postoperative hour was the main objective of this study. Methods: We conducted a prospective, single blind, randomized controlled trial. We enrolled 40 patients who underwent kidney transplantation from deceased donors. Patients randomized in the “PPV” group received fluids whenever PPV was higher than 12%, patients in the “free fluid” group received fluids following our institutional standard care protocol for kidney transplantations (10 mL.kg-1. h-1). Results: Urinary output was similar at every time-point between the two groups, urea was statistically different from the third postoperative day with a peak at the fourth postoperative day and creatinine showed a similar trend, being statistically different from the second postoperative day. Urea, creatinine and urine output were not different at the hospital discharge. Conclusion: PPV guided fluid therapy during kidney transplantation significantly improves urea and creatinine levels in the first week after kidney transplantation surgery. Resumo: Objetivo: Transplante renal é o tratamento padrão-ouro na doença renal em estágio terminal. Embora diferentes variáveis hemodinâmicas, tais como pressão venosa central e pressão arterial média, tem sido usadas para orientar a estratégia de reposição volêmica durante a cirurgia, a melhor estratégia ainda não foi determinada. A Variação da Pressão de Pulso (VPP) durante o ciclo respiratório é reconhecida como um bom preditor da resposta à infusão de volume para otimização hemodinâmica perioperatória no centro cirúrgico. O objetivo do estudo foi estudar se a estratégia de reposição de volume orientada por VPP é melhor do que a estratégia liberal de reposição de volume durante cirurgia de transplante renal.O principal objetivo do estudo foi identificar diferença no débito urinário na primeira hora do pós-operatório. Método: Realizamos estudo prospectivo, uni-cego, randomizado, controlado. Incluímos 40 pacientes submetidos a transplante renal de doador cadáver. Pacientes randomizados para o grupo “VPP” receberam volume quando a VPP estava acima de 12%, e os pacientes no grupo “reposição liberal” receberam volume de acordo com o nosso protocolo institucional padrão de assistência para transplante renal (10 mL.kg-1. h-1). Resultados: O débito urinário foi semelhante em todos os tempos nos dois grupos, a ureia foi estatisticamente diferente a partir do terceiro dia do pós-operatório com pico no quarto dia do pós-operatório e a creatinina apresentou tendência semelhante, tornando-se estatisticamente diferente a partir do segundo dia do pós-operatório. Ureia, creatinina e débito urinário não estavam diferentes na alta hospitalar. Conclusões: A terapia orientada por VPP durante transplante renal melhorou de forma significante os níveis de ureia e creatinina na primeira semana pós-transplante renal.